MODEL KOMUNIKASI POLITIK RIDWAN KAMIL DI MEDIA SOSIAL INSTAGRAM: KAJIAN SOSIOLINGUITIK - Ixsir Eliya; Ida Zulaeha (Department of Indonesia Language and Literature Teaching, UIN Syarif Hidayatullah Jakarta, 2017)
Abstract: Political communications can be done by using the selection of speech code in accordance with its purposes and functions. This study aims to find and describes instances, functions, and patterns of speech code which is selected by Ridwan Kamil in his Instagram's political communication as mayor of Bandung . The data are collected via observation method and other advanced techniques such as uninvolved conversation observation technique, documentation technique, and writing technique. The data are analyzed using Miles and Huberman analysis model, contextual method, and comparative method. The instance of Ridwal Kamil’s speech code selection in political communication in Instagram were 1) intra-code in English, formal Indonesian, and Sundanese; 2) code switching in the form of code switching, register switching , and variety switching ; 3) code mixing in the form of interpolation of word, phrase, clause, word-idiom, and word-phrase. The patterns of speech code selection of Ridwan Kamil in political communication was vertical pattern. The function of speech code selection were individual, cultural, communal and educational. Abstrak: Komunikasi politik dapat dilakukan dengan menggunakan pilihan kode tutur sesuai dengan tujuan dan fungsinya. Tujuan penelitian ini menganalisis wujud, pola, dan fungsi pilihan kode tutur Ridwan Kamil sebagai Wali kota Bandung dalam komunikasi politik di Instagram. Data dikumpulkan dengan metode simak menggunakan teknik simak bebas libat cakap (SBLC), teknik dokumentasi, dan teknik catat. Analisis data dilakukan dengan menggunakan model analisis Miles dan Huberman, metode padan, dan metode kontekstual. Wujud pilihan kode tutur Ridwan Kamil dalam komunikasi politik di Instagram meliputi 1) tunggal kode dan variasinya yang berupa kode Inggris, kode Indonesia ragam formal, dan kode Sunda; 2) alih kode yang berupa alih bahasa, alih register, dan alih ragam; serta 3) campur kode yang berupa penyisipan kata, frasa, klausa, kata-idiom, dan kata-frasa. Pola pilihan kode tutur Ridwan Kamil dalam komunikasi politik adalah pola vertikal. Fungsi pilihan kode tutur meliputi fungsi personal, kebudayaan, kemasyarakatan, dan pendidikan. Permalink/DOI: http://dx.doi.org/10.15408/dialektika.v4i2.5540.